Energy storage properties in Nd-doped AgNbTaO3 lead-free antiferroelectric ceramics with Nb-site vacancies - Zhilun Lu; Dongyang Sun; Ge Wang; Jianwei Zhao; Bin Zhang; Dawei Wang; Islam Shyha (Journal of Advanced Dielectrics, 2023)
It is crucial to discover lead-free materials with ultrahigh recoverable energy density ([Formula: see text][Formula: see text]) that can be employed in future pulse power capacitors. In this work, a high [Formula: see text][Formula: see text]of 4.51 J/cm3 was successfully obtained in lead-free Nd-doped AgNb[Formula: see text]Ta[Formula: see text]O3 antiferroelectric ceramics at an applied electric field of 290 kV/cm. It is discovered that Nd doping paired with Nb-site vacancies could stabilize the antiferroelectric phase by lowering the temperatures of the M1–M2 and M2–M3 phase transitions, which leads to higher energy storage efficiency. Furthermore, Nd and Ta co-doping will contribute to the electrical homogeneity and low electrical conductivity, resulting in large breakdown strengths. Aliovalent doping in Ag-site with Nb-site vacancies serves as a novel strategy for the construction of AgNbO3-based ceramics with excellent energy storage performance.